Jean, DREZE y Amartya, K. SEN (1989). Hunger and Public Action. Wider Studies in Economic Development. Oxford. Oxford University Press-Clarendon Press. - Vega-Centeno, Máximo (Economia, 1993)
Esta reseña no presenta resumen.